Comparison of production results between blue foxes housed with and without platforms - Korhonen, Hannu; Niemelä, Paavo (Agricultural and Food Science, 1995)
The production results of farmed blue foxes (Alopex lagopus) housed in cages with and without resting platforms were compared. No differences in weight gain or reproductive performance were found between the groups. However, locomotor activity prior to the breeding season tended to be slightly lower in animals provided with platforms. Platform use during the period of winter fur development (Oct-Nov) varied for the different platform constructions, being highest in wooden U-type platforms placed 30 cm from the cage roof (54.1% of observations on platforms) and lowest in the corner platform type (12.6%, p<0.001). Use of platforms made of wire mesh (45.2%) did not differ significantly from that of the wooden U-types. Ceiling and construction material affected platform dirtiness. The proportion of clean platforms was lowest (35.7%) when the platform was 30 cm from the roof. Net platforms remained very clean throughout the study. The time required for cleaning was greatest in August, ranging from 82 seconds/platform/week for the U-30 type to 2 seconds for the net type. Fur quality (p<0.001) and clarity (p<0.001) had a significant, but negative, correlation with platform dirtiness. The condition of almost all the wooden platforms deteriorated over time due to chewing. Wire mesh platforms were not chewed on. From the farmer’s point of view, wire mesh seems to be preferable to wood as a platform material.